A shared vision for climate security in Mali. A joint report to inform the national climate security strategy for Mali. - Sarzana, Carolina; Renkamp, Theresa Marie; Cisse, Sokhna Ramatoulaye; Ouedraogo, Yacouba; Hounnou, Emmanuel Fèmi; Meddings, George; Ramos, Cristina; Ouedraogo, Mathieu; Laderach, Peter; Pacillo, Grazia; Samaké, Oumar Baba; Wolter, Svenja; et al. (2024)
In response to these climate security implications, Mali and other Sahelian countries adopted a landmark declaration at the first Sahel Forum on Climate, Peace and Security held in Bamako, Mali, in November 2023. The Bamako declaration reflects the commitment of Sahelian countries to strengthening climate security in the region and serves as a catalyst for action at national, regional, and international levels in terms of development and financing. The Bamako forum critically assessed the quality of responses in the Sahel region to date and encouraged the development and implementation of innovative solutions that simultaneously address conflict prevention and management, sustainable natural resources management, climate change adaptation, and peacebuilding. In line with these objectives, Mali has since embarked on developing a national climate security strategy aimed at achieving the goals of the declaration. As part of the CGIAR’s Fragility, Conflict and Migration Initiative, the Climate Security team at the Alliance of Bioversity International and CIAT, in partnership with the United Nations Development Program (UNDP), the Malian Agency for the Environmental and Sustainable Development (AEDD) and the Liptako-Gourma Authority (ALG) co-hosted the first-national level workshop on climate, peace and security on 11-12 June 2024. This workshop, held within the context of the Bamako Declaration, addressed the complex and interconnected issues surrounding climate, peace, and security in Mali and gathered insights to guide the Malian technical committee in developing the national climate security strategy. Specifically, the workshop aimed to: 1) Validate the main pathways from climate to insecurity dynamics, using existing research and participants' expertise to identify potential research gaps, 2) Define action points for greater sensitivity to climate security in policies, programs, and investments and 3) Provide recommendations for developing the national climate security strategy, informing the technical committee with guidelines and scientific tools.